Expanding the Trichoderma harzianum species complex: Three new species from Argentine natural and cultivated ecosystems - Barrera, Viviana Andrea; Iannone, Leopoldo; Romero, Andrea Irene; Chaverri, Priscila (Taylor & Francis, 2025)
A study was performed on a collection of 84 isolates from decaying plant tissues and soils in Argentina previously identified as Trichoderma harzianum. Based on multiple phenotypic characters and multilocus phylogenetic analyses, 10 species were distinguished, three of which are described as new species: T. austroindianum, T. hortense, and T. syagri. Among the remaining seven identified species, the following five can be added to the Argentine mycobiota: T. afarasin, T. afroharzianum, T. endophyticum, T. guizhouense, and T. neotropicale. Trichoderma afroharzianum and T. endophyticum were the most frequent species found in the samples. In addition, a collection of isolates previously identified as T. harzianum with antagonistic abilities were reidentified as T. afroharzianum, thus highlighting the importance of correct identification of biocontrol species.